Biosynthetic labeling with 3-O-propargylcaffeyl alcohol reveals in vivo cell-specific patterned lignification in loquat fruits during development and postharvest storage. (10th March 2021) - Zhu, Nan; Zhao, Chenning; Wei, Yuqing; Sun, Chongde; Wu, Di; Chen, Kunsong
Abstract: Lignification is a major cell wall modification that often results in the formation of sophisticated subcellular patterns during plant development or in response to environmental stresses. Precise localization of the spatiotemporal deposition of lignin is of great importance for revealing the lignification regulatory mechanism of individual cells. In loquat fruits, lignification typically increases the flesh lignin content and firmness, reducing their edibility and processing quality. However, the precise localization of the spatiotemporal active zones of lignification inside loquat fruit flesh remains poorly understood, and little is known about the contribution of patterned lignification to cell wall structure dynamics and the subsequent fruit-quality deterioration. Here, we performed an emerging bioorthogonal chemistry imaging technique to trace the in vivo patterned lignification dynamics in cells of loquat fruit flesh during development and storage. In developing fruits, lignified cells (LCs) and vascular bundles (VBs) were the zones of active lignification, and ring-like LCs deposited lignin at both the inner wall layer and the outer periphery sides. The domino effect of the generation of LCs was preliminarily visualized. In mature fruits, the newly formed lignin in the flesh of fruits during storage was specifically deposited in the corners and middle lamellae of parenchyma cells surrounding the VBs, resulting in the development of a reticular structure. Based on the findings, distinct spatiotemporal patterned lignification modes for different flesh cells in loquat fruits were proposed. These findings provide loquat lignification dynamics together with spatiotemporal data that can improve our understanding of the lignification process in planta .